2012
DOI: 10.1124/jpet.112.191890
|View full text |Cite
|
Sign up to set email alerts
|

Durable Pharmacological Responses from the Peptide ShK-186, a Specific Kv1.3 Channel Inhibitor That Suppresses T Cell Mediators of Autoimmune Disease

Abstract: The Kv1.3 channel is a recognized target for pharmaceutical development to treat autoimmune diseases and organ rejection. ShK-186, a specific peptide inhibitor of Kv1.3, has shown promise in animal models of multiple sclerosis and rheumatoid arthritis. Here, we describe the pharmacokinetic-pharmacodynamic relationship for ShK-186 in rats and monkeys. The pharmacokinetic profile of ShK-186 was evaluated with a validated high-performance liquid chromatography-tandem mass spectrometry method to measure the peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 110 publications
(166 citation statements)
references
References 40 publications
4
162
0
Order By: Relevance
“…Toxicity studies with PAP‐1 and the peptidic K V 1.3 blocker ShK‐186 have so far not revealed any toxicity despite 6 months or 28 days of continuous administration in rats or rhesus macaques 4, 8. PAP‐1 has further completed IND‐enabling toxicity studies, while ShK‐186 has passed both IND toxicity studies and Phase‐1 safety studies without any adverse findings 6, 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity studies with PAP‐1 and the peptidic K V 1.3 blocker ShK‐186 have so far not revealed any toxicity despite 6 months or 28 days of continuous administration in rats or rhesus macaques 4, 8. PAP‐1 has further completed IND‐enabling toxicity studies, while ShK‐186 has passed both IND toxicity studies and Phase‐1 safety studies without any adverse findings 6, 9…”
Section: Discussionmentioning
confidence: 99%
“…Interest in Kv1.3 afterward waned but revived following reports from our group that Kv1.3 is overexpressed in activated CCR7 − effector memory T‐cells (T EM ) and that Kv1.3 blockers therefore constitute immunomodulators rather than general immunosuppressants 3, 4, 5. Subsequent proof‐of‐concept animal studies demonstrated that the Kv1.3 blocking sea anemone Stichodactyla helianthus peptide ShK and its derivatives treat rat models of multiple sclerosis and rheumatoid arthritis,4, 5, 6 while our small molecule Kv1.3 blocker PAP‐1 prevents autoimmune diabetes4 in rats and treats psoriasis in a mouse xenograft model 7. As Kv1.3 blockers preferentially target T EM cells, Kv1.3 blockers do not impair the ability to clear acute infections or develop vaccine responses.…”
Section: Introductionmentioning
confidence: 99%
“…ShK-186 treatment significantly reduced TNFα expression in visceral WAT (Fig. 2F), possibly via its known immunomodulatory effects on T cells and macrophages (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The low uncoupling protein 1 (UCP1) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The antiobesity effects of ShK-186 therapy are remarkably similar to the effects of Kv1.3 gene deletion in dietinduced obesity (Table S1), strongly suggesting that the antiobesity activities of ShK-186 are predominantly due to pharmacological actions on Kv1.3. These actions are due to blockade of Kv1.3 channels in peripheral tissues because <0.1% of the peptide crosses the blood-brain barrier (17). At least three mechanisms contribute to the antiobesity effects of ShK-186: BAT activation leading to increased energy expenditure, altered metabolism in the liver, and reduction of obesity-induced inflammation of abdominal WAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation